Evaluation of enhanced haemolysis agar for detection of Listeria spp. and L. monocytogenes from production lines of fresh to cold-smoked fish - Vaz-Velho, Manuela (2011)
Enhanced haemolysis agar (EHA) was compared to the two conventional Listeria isolation agars Oxford and PALCAM for its ability to detect Listeria spp. from production lines of fresh to cold-smoked fish. The ability of EHA for distinguishing L. monocytogenes colonies from other Listeria spp. was also evaluated. A total of 243 fish and environmental samples were analysed. Overall, 42 samples were found to contain Listeria spp. Only 34 samples were positive simultaneously by the three plating media. Two samples considered to be negative by the two conventional agars were found to be positive after isolation on EHA. All three selective agars were shown to be less effective in recovering Listeria spp. after primary enrichment in half-Fraser broth, compared to secondary enrichment in Fraser broth after 24 and 48 h. From 79 Listeria but presumptive negative L. monocytogenes colonies, EHA identified correctly 76 Listeria spp. and presented three false-negative results_three colonies further identified as L. monocytogenes but showing no noticeable haemolysis on EHA. Twenty-three of the thirty-three L. monocytogenes presumptive positive colonies, were confirmed positive and ten were identified as L. seeligeri. Despite its ability of distinguishing L. monocytogenes from the other Listeria spp., unless it is produced as a commercial medium, EHA cannot be an alternative to time-consuming classical identification because the preparation of this medium is both time and labour intensive.